Infection and Foot Care in Diabetics Seeking Treatment in a Tertiary Care Hospital, Bhubaneswar, Odisha State, India. (4th August 2015) - Kar, Sonali; Ray, Shalini; Meher, Dayanidhi
Abstract : Diabetes mellitus is a major public health problem that can cause a number of serious complications. Foot ulceration is one of its most common complications. Poor foot care knowledge and practices are important risk factors for foot problems among diabetics. The present study was undertaken in the diabetes outpatient department of a tertiary care hospital to assess the practices regarding foot care in diabetes, find out the determinants of foot ulcer in diabetics, and offer suggestions to improve care. After informed consent, a total of 124 diabetics were interviewed to collect all relevant information. The diabetic foot care practice responses were converted into scores and for the sake of analysis were inferred as poor (0–5), fair (6-7), and good (>7) practices. Of the study population, 68.5% (85/124) consisted of men. The disease was diagnosed within the last 5 years for 66% (81/124) of the study participants. Of the study subjects, 83% (103/124) were on oral hypoglycemic agents (OHAs), 15.3% (19) on insulin, and 2 on diet control only. Among them about 18.5% had a history of foot ulcer. 37.9% reported using special slippers, 12% diabetics used slippers indoors, and 66.9% used slippers while using toilet. Of the study subjects, 67.8% said that feet should be inspected daily. 27.4% said they regularly applied oil/moisturizer on their feet. There is a need on part of the primary or secondary physician and an active participation of the patient to receive education about foot care as well as awareness regarding risk factors, recognition, clinical evaluation, and thus prevention of the complications of diabetes.